Peran Orang Tua Terhadap Hasil Belajar Siswa Pada Pembelajaran Daring - Zulfatun Na'im; Eva Luthfi Fakhru Ahsani (PEDAGOGIKA, 2021)
This article aims to find out: 1) what is the role of parents on student learning outcomes? 2) what is the role of parents in online learning ?, 3) What are the efforts made by parents in improving student learning outcomes in online learning ?. Parents are one of the people who are very responsible in the process of children's education. The active role of parents during the Covid-19 pandemic by implementing online learning will have an impact on student learning outcomes. The research method used in this research is qualitative research methods and in data collection using the phenomenological method and the research subjects are parents. From the research that has been carried out, the results of this study are: The role of parents on student learning outcomes is very important, with the responsibility of that person, student learning outcomes will affect especially learning outcomes related to affective and psychomotor, parental war in learning online during the Covid-19 pandemic is very influential and very important, with the role of parents in this online learning, the child will complete the task that has been given, and the child's ability to continue to develop even though not with the accompanying teacher. The efforts made by parents are always to motivate and encourage children to be able to carry out online learning.